The effect of equine-facilitated intervention on the development of communication skills in children with neurodevelopmental disorders - Viola Jónová; Markéta Janatová; Lucie Hovorková; Xenia Svobodová (Listy klinicke logopedie, 2021)
Equine-facilitated intervention encompasses activities and therapies in areas where the horse and the person with health or social disadvantages or special needs meet. The intervention may focus on motor, psychological, social or educational areas, depending on the individual client's equine-facilitated intervention goals. By combining Speech Therapy and equine-facilitated intervention, a comprehensive intervention is provided for the client with impaired communication skills, by utilising horses, ponies and related activities. The equine-facilitated intervention can be individual or group, and some equine-facilitated intervention programmes also involve family members and caregivers. In studies of the effect of equine-facilitated intervention on children with neurodevelopmental disorders, positive effects of equine-facilitated intervention have been observed on attention, hyperactivity, vocabulary development, social interaction, communication, facilitation of eye contact and improved language skills, in addition to motor function. With the appropriate choice of intervention goals and methods, equine-facilitated intervention can promote improvement in clients' condition to the extent of their functional potential and thus enhance quality of their life.